РЕГУЛЮВАННЯ ЗАЙНЯТОСТІ ЯК ФАКТОР РОЗВИТКУ ЕКОНОМІКИ КРАЇНИ В КОНТЕКСТІ ЄВРОПЕЙСЬКОЇ ІНТЕГРАЦІЇ (International Journal of Innovative Technologies in Economy, 2018)
The article deals with employment and unemployment problems of the population of Ukraine. On the basis of statistical data, an analysis of the system of socio-economic relations related to providing economically active population with workplaces and its participation in socially useful activities is carried out. The analysis of the problem makes it possible to point out that the socio-economic development of Ukraine should provide an opportunity to implement the labor aspect of the life of the population and a sufficient level of its income. Restrictions or lack of conditions for the realization of labor potential creates preconditions for labor migration. The flows of labor migrants reflect local labor markets through a significant outflow of the able- bodied population, which leads to social strain. It ultimately contributes to the liquefaction of the rural settlements network due to the disappearance of few small communities. State regulation of employment on the basis of market regulators is connected with professional labor markets, the formation of which in different regions has specific features. It is determined that the state promotes effective employment of the population, in particular by developing and implementing state and regional employment programs, optimizing the objects of education, health care, social protection, consumer services.